Network Distribution Model of Influenza Virus in the Community - P. Pongsumpun (My University, 2018)
Influenza is occurred around the world.It caused by influenza virus.The types of influenza can affect people such as type A, B and C. The influenza virus can spread though the air from coughs or sneezes between people.It can be found in all age of human.In this study, we formulate the network model for the transmission of influenza virus.The numerical simulations are given to see the influence of each parameter.The mathematical method is used in this paper.The discussion of each parameter is given.
Keywords: Influenza Virus Research Studies